Feasibility of self-sampling and human papillomavirus testing for cervical cancer screening in First Nation women from Northwest Ontario, Canada: a pilot study. Issue 1 (26th February 2011) - Zehbe, Ingeborg; Moeller, Helle; Severini, Alberto; Weaver, Bruce; Escott, Nicholas; Bell, Crystal; Crawford, Sandra; Bannon, Diane; Paavola, Natalie
Abstract : Background: The incidence of cervical cancer is up to sixfold higher among First Nation women in Canada than in the general population. This is probably due to lower participation rates in cervical cancer prevention programmes. Objective: To raise screening participation in this underserved population by launching an alternative approach to (Pap)anicolaou testing in a clinic—namely, vaginal self-sampling followed by human papillomavirus (HPV) diagnostics. Methods: Good relationships were established with a First Nation community of the Northern Superior region in Northwest Ontario, and then 49 community women, aged 25–59, were recruited, who provided a vaginal self-sample and answered a questionnaire. Frequency distributions and cross-tabulations were used to summarise the data. Associations between categorical variables were assessed using the χ 2 test of association, or the Goodman–Kruskal γ if both variables had ordered categories. Self-collected samples were tested for integrity and HPV using optimised molecular biological methods. Results: The majority of participants (87.2%) were amenable to future HPV screening by self-sampling. This finding was independent of age, educational level and a previous history of abnormal Pap tests. Interestingly, the preferred way to learn about sexual health remained through interaction with healthcare professionals. As defined by the presence of a housekeeping gene, self-sample integrity was high (96%). Using polymerase chain reaction-based Luminex typing, the overall HPV positivity was 28.6% (ie, with either a low- or high-risk type) and 16.3% were infected with a high-risk type such as HPV16. Conclusion: In this pilot study of First Nation women, self-sampling and HPV testing was well received and self-sample quality was excellent. A larger survey to be conducted in other Northern Superior communities in Northwest Ontario will determine whether this approach could become a viable screening strategy for First Nation women.